Integration of Leadership Values in Civil Apparatus Career Development at BKPSDM Kab. Bolaang Mongondow Utara - Bolilio, Sri Wilanda; Ansar, Ansar; Zulystiawati, Zulystiawati (Darul Yasin Al Sys, 2025)
This study examines the integration of leadership values into employee career development, aiming to identify and describe the specific values embedded in this process. Adopting a qualitative design, seven participants were purposively selected based on their roles and responsibilities relevant to the study. Data were collected through interviews, observations, and documentation, and analyzed using thematic analysis. Findings reveal that the core leadership values integrated into career development include accountability, fairness, and integrity, supported by values such as exemplary behavior, responsibility, honesty, and authoritarianism. These values form the basis for a career development system that is fair, transparent, and focused on enhancing the competence and qualifications of civil servants.